Analysis of factors affe cting the post-appendectomy wound healing process at RSU Haji Medan in 2021-2023 - Kartika, Tasya Surya; Suhaymi, Ery; Lubis, Taufik Akbar Faried; Lubis, Debby Mirani (Science Midwifery, 2024)
Appendicitis is an inflammation of the appendix or appendix that can occur in anyone, causing abdominal pain. Risk factors for appendicitis include age, gender, diet, and family history. This is due to poor diet at that age. Treatment for appendicitis can be done by surgery. Appendectomy surgery is performed by appendectomy, which is a surgical procedure to remove the inflamed appendix. Normal surgical wound healing is influenced by various factors, namely coagulation, immune system disorders, nutrition, chronic diseases, medications, and suturing techniques. This study was conducted to determine what factors play a role in the wound healing process in post-appendectomy patients. To determine the factors that play a role in the healing of post-appendectomy patients at the Haji General Hospital in Medan in 2021-2023. Descriptive research with a retrospective design that takes data through medical records from 2021-2023. It was found that post-appendectomy patients were more in early adolescence (12-16 years) and late adulthood (36-45 years), with male gender who had a normoweight nutritional status with dry wound conditions with a high number of leukocytes (leukocytosis) and often occurred in the acute appendicitis type. Post-appendectomy patients at the Haji Medan General Hospital in 2021-2023 were mostly found in early adolescence (12-16 years) and late adulthood (36-45 years), male gender, nutritional status with the normoweight category, had dry wound conditions, with a high number of leukocytes (leukocytosis), and patients suffering from acute appendicitis.